The Value of Islamic Boarding Schools, Countering the Radical Understanding of Terrorism - Saefrudin (Proceedings of Annual Conference on Community Engagement, 2022)
any cases that occur in the community regarding the radical ideology of terrorism have led to anarchic acts which incidentally are alumni of the Middle East (Pakistan) or modern Islamic boarding schools who have a textual understanding of the nature, so that many of them have extreme characters, claim to be self-righteous, often blame other groups. one Muslim, such an understanding must be anticipated from an early age so that it does not spread to others. The values ​​of the pesantren are a solution to counteract radical schools of terrorism as implemented in the Tebuireng Jombang Islamic boarding school, where the Tebuireng Islamic boarding school is the oldest Islamic boarding school that studies books such as hadith and fiqh. Therefore, in the era of modern digitalization, which is full of rapid information, it has a very large and widespread impact when the information is related to the ideology of terrorist radicalism, it is possible that these streams will enter Islamic boarding schools, especially Islamic boarding schools, which target teenage students who are emotionally unable to do so. controlled by the values ​​of the Islamic boarding school that adopts Islamic values, it will provide a solution. As the values ​​of Pesantren Tebuireng that have been taught by K.H. Hasyim Asy'ari and K.H. Salahudin Wahid, such as: the values ​​of honesty, sincerity, hard work, responsibility, brotherly tolerance. the values ​​above will provide solutions to students, especially the values ​​of tolerance, honesty and responsibility with these solutions, in the future the students will be protected from the dangers of understanding radicalism terrorism, will also become students who understand religious knowledge as a whole and provide benefits to make Islam rahmatan lill alamin as the message of KH Hasyim Asy'ari, first about brotherhood, two sciences, science is able to unite various groups with different understandings into one unit,